Caracterización del fenotipo de resistencia antibiótica en bacterias que colonizan a mascotas caninas - Benites-Azabache, Juan Carlos (2025)
The antibiotic resistance phenotype of bacteria colonizing canine pets was characterized. One hundred domestic dogs from kennels were sampled. Bacterial identification and sensitivity testing was performed using the VITEK® 2 system, and phenotypes were confirmed according to the Clinical and Laboratory Standards Institute (CLSI) methodology. A total of 408 microorganisms were isolated, of which 57% were Enterobacteriaceae, 23% Staphylococcus, 10% non-fermenting Gram-negative bacilli, and 5% enterococci. Moreover, 80% of Staphylococcus strains were methicillin-resistant, E. faecalis was the only bacterium of its genus to exhibit resistance to gentamicin and vancomycin, 57% of Enterobacteriaceae were β-lactamase producers, while 10% of non-fermenting Gram-negative bacilli were carbapenemase-positive. The characterization of the antibiotic resistance phenotype in bacteria colonizing canine pets revealed a worrying prevalence of multidrug-resistant strains. These results highlight the need for ongoing and rigorous monitoring of antibiotic resistance in pets.